Venlafaxine Hydrochloride Controlled Release Bilayer Tablets: Optimization of Formulation Variable by Using Dyspnea on Exertion (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The current research work was to develop bilayer tablet of venlafaxine hydrochloride to increase drug efficacy for efficient treatment of depression. The satisfactory result of treatment can be achieved upon the maintenance of drug concentration within an effective level in the body, so a uniform and constant drug supply are desirable. An immediate layer of venlafaxine HCl was formulated using super disintegrants, i.e., croscarmellose sodium (CCS) and sodium starch glycolate (SSG); tablet compact by direct compression. HPMC K100M and ethylcellulose (EC) were utilized as release retarding polymers in sustained release layer by wet granulation technique with the help of PVP K30 in IPA solution (10%) as a granulating agent. Full 32 factorial designs were used to find out the optimum quantity of release retardant polymers. Bilayer tablet was evaluated for various parameters, i.e. hardness, friability, weight variation, % drug content, disintegration time (IR layer), and % drug release study. Statically, an analysis was carried out using factor X1 (HPMC K100M) and X2 (EC) for dependent variable % drug release at 8, 12, and 20 hours. A formulation was optimized and a formulation containing 305.36 mg of HPMC K100M and 54.03 mg of ethyl cellulose. Optimized formulation show 47.12 ± 2.1, 59.89 ± 2.2, and 89.06 ± 2.3 drug release at 8, 12, and 20 hours, respectively, which is almost similar to theoretical dose calculation with similarity factor f2 97, 99, and 98%, respectively. Bilayer tablet formulation was observed to be stable and fulfilled all compendia specifications.